Integrasi Pendidikan Agama Islam dengan Bimbingan Konseling dan Dampaknya Terhadap Akhlak Peserta Didik - Sumarta Tata; Djenal Suhara; Windi Nur Wulandini (TA'DIB: Jurnal Pendidikan Agama Islam, 2024)
This research constitutes a literature review that explores the integration of Islamic Religious Education (PAI) with Counselling Guidance (BK) and its influence on the moral development of students. The methodology adopted involves a thorough examination of various literature sources, including academic journals, books, and previous studies, with the aim of identifying the concepts, strategies, and outcomes of this integration. The analytical approach employed includes an in-depth content analysis of relevant literature to investigate the effective integration of PAI and BK. The study discusses theoretical foundations, strategies for implementing PAI and BK integration, an analysis of its impact on the moral development of students, and the challenges faced in its application. The results indicate that integrating PAI with BK significantly contributes to the enhancement of students' moral understanding and character formation. This research highlights the importance of collaboration between PAI teachers and BK counsellors, as well as the need for strong policy support, to fully realise the benefits of this integration.